A Quantum Chaos Clonal Multiobjective Evolutionary Method Reasearch - Shuyue Wu (Institute of Advanced Engineering and Science, 2016)
A quantum chaos cloning multi-objective evolutionary algorithm was proposed herein based on chaos search ergodicity, quantum computing efficiency and clonal selection theory of antibodies in artificial immune system. The qubits encoded initial population is used in the new algorithm, Chaos quantum rotation gates are introduced to update individuals, crowding distance is used to keep solution population distribution and diversity. Theoretical analysis and simulation show the effectiveness of the algorithm.